Calcium-aluminum composite emulsion as well as preparation method and application thereof

By preparing a calcium-aluminum composite emulsion, using a combination of composite powder of calcium oxide and aluminum oxide powder with surfactants and sustained-release agents, the problems of low effective calcium content and poor permeability of traditional lime agents are solved, and efficient removal of phosphorus and fluorine is achieved. The effect is to ensure that the treated waste meets environmental protection standards.

CN119330480AActive Publication Date: 2025-01-21WENGFU (GRP) CO LTD +2
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411771722.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-04
Publication Date
2025-01-21
Estimated Expiration
2044-12-04

AI Technical Summary

Technical Problem

Traditional lime agents are unable to remove phosphorus and fluorine efficiently at the same time due to their low effective calcium content and poor permeability, resulting in unsatisfactory treatment results, and the waste after treatment may still have a risk of environmental pollution.

Method used

Calcium oxide and aluminum oxide powder are ball-milled to prepare composite powder, and surfactants and sustained-release agents are added, and a calcium-aluminum composite emulsion is prepared through steps such as stirring and standing.

Benefits of technology

The effective calcium content and permeability of the composite emulsion are improved, which can deeply remove phosphorus and fluorine, reduce the content in wastewater, make the treatment process more efficient, and ensure that the treated waste meets environmental protection standards.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119330480A_ABST
    Figure CN119330480A_ABST
Patent Text Reader

Abstract

The invention discloses a calcium-aluminum composite emulsion and a preparation method and application thereof, and belongs to the technical field of industrial solid waste treatment and environmental protection. The settling agent is mainly prepared from aluminum oxide and calcium oxide composite powder, and is high in settling rate and good in settling effect. The preparation method comprises the following steps: carrying out ball milling treatment on aluminum oxide and calcium oxide, adding nonionic polyoxyethylene amide and nonionic polyacrylamide, stirring, and dropwise adding ethylene glycol in the stirring process to prepare a calcium-aluminum composite emulsion; the effective calcium content, the permeability and the precipitation performance of the calcium-aluminum composite emulsion are improved by adopting aluminum oxide and subsequent ball milling treatment, then phosphorus and fluorine pollutants in phosphorus and fluorine wastewater and phosphogypsum can be rapidly and effectively precipitated, the treated phosphogypsum conforms to first-class solid waste, and the treated phosphorus and fluorine wastewater also conforms to the national standard. The technical problem that phosphorus and fluorine cannot be efficiently removed at the same time due to low effective calcium content and poor permeability of a traditional lime agent is solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of industrial solid waste treatment and environmental protection, and specifically relates to a calcium aluminum composite emulsion and a preparation method and application thereof. Background Art

[0002] The phosphogypsum and phosphorus chemical wastewater produced by the phosphoric acid industry will have a serious impact on the environment. It is very urgent to solve the harm of pollutants to the environment.

[0003] Traditionally, lime neutralization and solidification methods are often used to treat phosphogypsum and phosphorus chemical wastewater harmlessly. Lime neutralization is an effective treatment method that can solidify harmful components in phosphogypsum and convert it into a type of solid waste. This method has the advantages of simple process route and low investment, and is particularly suitable for phosphogypsum with low organic matter content and stable quality.

[0004] However, traditional lime reagents have problems such as low effective calcium content and poor permeability. For example, on the one hand, the effective calcium content of traditional lime reagents is often low, which means that when treating phosphogypsum and phosphorus chemical wastewater, a large amount of lime needs to be added to achieve the expected treatment effect, which not only increases the treatment cost, but also may introduce new pollution problems due to excessive addition; on the other hand, the dispersibility and permeability of lime particles in wastewater are poor, resulting in insufficient contact with pollutants in the wastewater and low reaction efficiency. This will affect the treatment effect and make it difficult to completely remove phosphorus and fluorine in the wastewater; at the same time, when treating phosphorus chemical waste, the traditional lime neutralization method is difficult to achieve the three indicators of soluble phosphorus, soluble fluorine and pH value after phosphorus chemical waste treatment. This means that the treated waste may still have environmental pollution risks and cannot meet the increasingly stringent environmental protection regulations. Summary of the invention

[0005] In order to overcome the shortcomings of the above-mentioned prior art, the purpose of the present invention is to provide a calcium aluminum composite emulsion and its preparation method and application, so as to solve the technical problem that traditional lime agents cannot simultaneously and efficiently remove phosphorus and fluorine due to low effective calcium content and poor permeability.

[0006] In order to achieve the above object, the present invention adopts the following technical solutions: The invention discloses a calcium aluminum composite emulsion, comprising: ball-milling calcium oxide and aluminum oxide powder to obtain composite powder, adding a surfactant to perform a first stirring, and adding a sustained-release agent dropwise during the stirring process, standing for 2 hours, adding water to the reaction system to perform a second stirring, and naturally cooling to room temperature to obtain the calcium aluminum composite emulsion.

[0007] Preferably, the composite powder of calcium oxide and aluminum oxide powder has an effective content of calcium and aluminum of ≥80%.

[0008] Preferably, the mass ratio of calcium oxide to aluminum oxide powder is (14-15): (5-6).

[0009] Preferably, dry milling is used for ball milling, agate beads with a diameter of 10 mm are used for ball milling, the rotation speed is set to 250 rpm, and the ball milling time is 2-3 h, so that 85% of the calcium oxide and aluminum oxide particles have a particle size of less than 200 mesh.

[0010] Preferably, the surfactant is non-ionic polyoxyethylene amide and non-ionic polyacrylamide (PAM), and the mass ratio of the two is (1-2): (2-3).

[0011] Preferably, the mass ratio of the composite powder to the nonionic polyoxyethylene amide and nonionic polyacrylamide (PAM) is 200:(1-2):(2-3).

[0012] More preferably, the polyoxyethylene amide nonionic surfactant and nonionic PAM are commercially available products, wherein the molecular weight of PAM is 5 million.

[0013] Preferably, the sustained-release agent includes one of ethylene glycol, methanol, propylene glycol or butanol, and the added amount is: 3-5 ml of the sustained-release agent per 100 g of calcium oxide and aluminum oxide powder.

[0014] More preferably, the sustained-release agent is used to control the hydration process of the composite powder, and a commercially available product with a purity of 99% is used.

[0015] Preferably, calcium oxide and aluminum oxide are commercially available products, and the effective calcium and effective aluminum contents are ≥80%.

[0016] Preferably, 100 ml of water is added per 10 g of the composite powder.

[0017] Preferably, the first stirring time is controlled within 5-10 minutes to allow the composite powder to fully contact with the surfactant; the second stirring time is at least 2-3 hours to allow the temperature of the reaction system to drop to room temperature. If the stirring time is too short, the composite powder cannot be completely emulsified; if the stirring time is too long, it will react with carbon dioxide in the air to generate other insoluble substances, reducing the effective content.

[0018] The invention discloses a calcium-aluminum composite emulsion prepared by the preparation method.

[0019] The present invention also discloses the use of the calcium aluminum composite emulsion in the harmless treatment of phosphogypsum. For phosphogypsum with soluble phosphorus of 20-1000 mg / L and soluble fluorine of 10-7000 mg / kg, a composite emulsion with effective calcium and aluminum content accounting for a certain proportion of the dry basis mass of the phosphogypsum is added. After 12-24 hours of curing reaction, the soluble phosphorus in the phosphogypsum is less than 0.5 ppm, the soluble fluorine is less than 10 ppm, and the pH value is maintained at 8-10, which meets the requirements of Class I solid waste. After the treated phosphogypsum is exposed to air and stacked for 1 month, the removal rates of soluble phosphorus and soluble fluorine are maintained at 99.3% and 98.4% respectively, and the concentrations are both lower than the national standards.

[0020] The present invention also discloses the application of the calcium aluminum composite emulsion in the treatment of phosphorus and fluoride wastewater. For phosphorus and fluoride wastewater with a phosphate concentration of 10 to 1000 mg / L, a fluoride ion concentration of 10 to 450 mg / L, and a pH value lower than 4, the emulsion is added to a pH value of 10-11. After reacting for 2 to 5 minutes, the phosphate concentration is lower than 0.5 mg / L, and the fluoride ion concentration is lower than 10 mg / L.

[0021] Compared with the prior art, the present invention has the following beneficial effects: The preparation method of the calcium aluminum composite emulsion disclosed in the present invention breaks through the technical defects of traditional lime reagents. First, the present invention uses a composite powder formed by calcium oxide and aluminum oxide as a raw material to prepare the calcium aluminum composite emulsion. The calcium aluminum composite component has a strong affinity for fluoride ions and phosphate ions, and can deeply remove these pollutants, reducing the content in the wastewater to a very low level, making the treatment process more efficient. In addition, the use of aluminum oxide powder, on the one hand, improves the precipitation performance of the composite emulsion, and can improve the precipitation performance of the generated product when treating phosphorus chemical waste, so that the treatment effect can be stabilized; on the other hand, aluminum oxide is an amphoteric compound, and the use of aluminum oxide powder can control the sudden change of the pH value of the reaction system caused by excessive addition during the treatment process, so that the three indicators of soluble phosphorus, soluble fluorine and pH value after the phosphorus chemical waste is treated are up to standard, meeting the national emission standards and resource recovery requirements, thereby solving the environmental problems generated in the phosphorus chemical production process. Secondly, the ball-milled calcium oxide and aluminum oxide powders are mixed with different types of sustained-release agents and surfactants to improve the emulsification degree of the composite powder. The ball-milled composite powder and spherical abrasive are subjected to high-speed friction and collision in the ball mill. This mechanical action can break the powder particles, reduce the particle size of the solid material and reduce the dispersion resistance between particles. Smaller particle size helps to increase the specific surface area of ​​the powder, improve its dispersibility, make the emulsification more complete, and increase the effective calcium content of the emulsion. At the same time, the reduction of the powder particle size directly leads to an increase in the specific surface area, which increases the contact area between the powder particles and the liquid, which is conducive to improving the permeability of the powder in the liquid and achieving the effect of rapid dispersion, thereby increasing the stability and rheology of the composite emulsion. The use of surfactants greatly increases the dispersibility and precipitation of the calcium aluminum component, promotes its full contact with soluble phosphorus and fluorine pollutants in the phosphogypsum to be treated, and the effect after treatment is stable. Again, the first stirring operation is performed to allow the surfactant to fully and evenly cover the surface of the powder particles. The sustained-release agent is added dropwise during the preparation process to effectively control the hydration process of the composite powder. This slow-release effect enables the emulsion to play a role in the wastewater treatment process continuously and stably, avoiding fluctuations in the treatment effect caused by a one-time large-scale release. A second stirring is then performed to ensure that the water and the components in the reaction system are fully mixed. The present invention solves the technical problem that the traditional lime reagent cannot simultaneously and efficiently remove phosphorus and fluorine due to low effective calcium content and poor permeability.

[0022] Furthermore, in the preparation method of the present invention, the surfactant is a nonionic polyoxyethylene amide and a nonionic polyacrylamide, wherein the polyoxyethylene amide surfactant contains a polyoxyethylene chain, has good surface activity, is suitable for reducing interfacial tension, and can provide surface activity. The polyoxyethylene amide surfactant has a good emulsifying effect, can stabilize emulsions and suspensions, and has strong adaptability, and can adapt to water with different pH values ​​and different hardness. Nonionic polyacrylamide (PAM) PAM can make the precipitate generated during the treatment fully settle down, reduce the precipitation time, enhance the treatment effect, and at the same time improve the rheological properties and increase the flocculation effect and solidification effect, and also improve the penetration performance of the emulsion and enhance the mass transfer performance.

[0023] The present invention discloses a calcium aluminum composite emulsion prepared by the above-mentioned preparation method, which has the advantages of being able to quickly and efficiently simultaneously precipitate phosphorus and fluorine pollutants in water bodies and phosphogypsum, and can simultaneously meet the corresponding national standards for pH value, phosphorus and fluorine, and has a stable precipitation effect and is not easy to be reversely released.

[0024] The calcium aluminum composite emulsion prepared by the present invention has the characteristics of flexibility and strong adaptability, and can be adjusted and optimized according to the different properties and processing requirements of phosphogypsum. When applied to the harmless treatment of phosphogypsum, its effectiveness, economy and stability are guaranteed, and it can provide higher effective calcium content and alkalinity during the solidification process, thereby enhancing the solidification effect, reducing the occupation of land resources, and avoiding the pollution of groundwater and surrounding soil by leachate. Experiments show that the soluble phosphorus in the phosphogypsum treated with the calcium aluminum composite emulsion is less than 0.5ppm, the soluble fluorine is less than 10ppm, and the pH value is maintained at 8-10, which meets the requirements of Class I solid waste; after the treated phosphogypsum is exposed to air for 1 month, the removal rates of soluble phosphorus and soluble fluorine are maintained at 99.3% and 98.4%, respectively, and the concentrations are lower than the national standards. Therefore, it has a wide range of application prospects, can be promoted and applied in the wet phosphoric acid industry, promote the sustainable development of enterprises, and make positive contributions to environmental protection. In addition, the high permeability calcium aluminum composite emulsion can also be used for the treatment of phosphorus-fluorine-containing wastewater, and also achieves good results.

[0025] Furthermore, the calcium aluminum composite emulsion also has efficient precipitation performance. Experimental results show that after the emulsion is added to the simulated wastewater, it can fully react with the fluoride ions and phosphate ions in the wastewater in a short time (such as within 0.5 hours) to form an insoluble precipitate. This rapid reaction ability is due to the strong affinity of the calcium aluminum composite component in the emulsion for fluoride ions and phosphate ions, which can deeply remove these pollutants and reduce the content in the wastewater to a very low level, making the treatment process more efficient. Experiments show that in the simulated wastewater treated with the calcium aluminum composite emulsion, the phosphate concentration is lower than 0.5 mg / L and the fluoride ion concentration is lower than 10 mg / L, which proves that the calcium aluminum composite emulsion prepared by the present invention has an efficient removal effect on the fluoride ions and phosphate ions in the simulated wastewater. In summary, the calcium aluminum composite emulsion prepared by the present invention has a wide range of application prospects. It can be seen that the calcium aluminum composite emulsion prepared in this application solves the technical problem that the traditional lime neutralization method is difficult to achieve the three indicators of soluble phosphorus, soluble fluorine and pH value after phosphorus chemical waste treatment. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 This is a real photo of the novel calcium aluminum composite emulsion prepared in Example 1; Figure 2 This is the change curve of soluble phosphorus and fluorine over time for phosphogypsum solidification in Example 10; Figure 3 This is the phosphorus and fluorine change curve for phosphorus and fluorine wastewater treatment in Example 11. DETAILED DESCRIPTION

[0027] In order to enable those skilled in the art to better understand the scheme of the present invention, the technical scheme in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.

[0028] It should be noted that the terms "first", "second", etc. in the specification and claims of the present invention and the above-mentioned drawings are used to distinguish similar objects, and are not necessarily used to describe a specific order or sequence. It should be understood that the data used in this way can be interchanged where appropriate, so that the embodiments of the present invention described herein can be implemented in an order other than those illustrated or described herein. In addition, the terms "including" and "having" and any variations thereof are intended to cover non-exclusive inclusions, for example, a process, method, system, product or device that includes a series of steps or units is not necessarily limited to those steps or units that are clearly listed, but may include other steps or units that are not clearly listed or inherent to these processes, methods, products or devices.

[0029] The present invention is further described in detail below with reference to the accompanying drawings and embodiments: Example 1 At room temperature and pressure, 15 g of calcium oxide and 5 g of aluminum oxide were ball-milled. The ball-milling method was dry milling. The ball-milling beads were agate beads with a diameter of 5 mm. The speed was set to 250 rpm. The ball-milling time was 2 h. To the ball-milled composite powder, 0.01 g of polyoxyethylene amide nonionic surfactant and 0.02 g of nonionic PAM were added in sequence, and 0.6 ml of ethylene glycol was added dropwise while stirring thoroughly with a glass rod, and the stirring was continued for 5 min, followed by standing for 2 h. After adding 200 ml of water, stirring was continued for another 3 h. When the temperature dropped to room temperature, a calcium aluminum composite emulsion was obtained. The dynamic viscosity was measured and the measured value was 0.31 Pa·s. The calcium aluminum composite emulsion had a high rheological property.

[0030] Example 2 At room temperature and pressure, 15 g of calcium oxide and 5 g of aluminum oxide were ball-milled. The ball-milling method adopted was dry milling. The ball-milling beads used were agate beads with a diameter of 5 mm. The speed was set to 250 rpm. The ball-milling time was 2.5 h. To the ball-milled composite powder, 0.02 g of polyoxyethylene amide nonionic surfactant and 0.03 g of nonionic PAM were added in sequence, and 0.6 ml of ethylene glycol was added dropwise while stirring thoroughly with a glass rod. The stirring was continued for 5 min, and then allowed to stand for 2 h. After adding 200 ml of water, stirring was continued for 3 h. When the temperature dropped to room temperature, a calcium aluminum composite emulsion was obtained. The dynamic viscosity was measured and the measured value was 0.32 Pa·s. The calcium aluminum composite emulsion had a high rheological property.

[0031] Example 3 At room temperature and pressure, 14 g of calcium oxide and 6 g of aluminum oxide were ball-milled. The ball-milling method was dry milling. The ball-milling beads were agate beads with a diameter of 5 mm. The speed was set to 250 rpm. The ball-milling time was 2 h. To the ball-milled composite powder, 0.01 g of polyoxyethylene amide nonionic surfactant and 0.02 g of nonionic PAM were added in sequence, and 1 ml of ethylene glycol was added dropwise while stirring thoroughly with a glass rod. The stirring was continued for 5 min, and then allowed to stand for 2 h. After adding 200 ml of water, stirring was continued for 3 h. When the temperature dropped to room temperature, a calcium aluminum composite emulsion was obtained. The dynamic viscosity was measured and the measured value was 0.33 Pa·s. The calcium aluminum composite emulsion had a high rheological property.

[0032] Example 4 At room temperature and pressure, 14 g of calcium oxide and 6 g of aluminum oxide were ball-milled. The ball-milling method adopted was dry milling. The ball-milling beads used were agate beads with a diameter of 5 mm. The speed was set to 250 rpm. The ball-milling time was 3 h. To the ball-milled composite powder, 0.01 g of polyoxyethylene amide nonionic surfactant and 0.02 g of nonionic PAM were added in sequence, and 0.7 ml of ethylene glycol was added dropwise while stirring thoroughly with a glass rod. The stirring was continued for 5 min, and then allowed to stand for 2 h. After adding 200 ml of water, stirring was continued for 3 h. When the temperature dropped to room temperature, a calcium aluminum composite emulsion was obtained. The dynamic viscosity was measured and the measured value was 0.33 Pa·s. The calcium aluminum composite emulsion had a high rheological property.

[0033] Example 5 At room temperature and pressure, 14 g of calcium oxide and 6 g of aluminum oxide were ball-milled. The ball-milling method adopted was dry milling. The ball-milling beads used were agate beads with a diameter of 5 mm. The speed was set to 250 rpm. The ball-milling time was 3 h. To the ball-milled composite powder, 0.01 g of polyoxyethylene amide nonionic surfactant and 0.02 g of nonionic PAM were added in sequence, and 0.8 ml of methanol was added dropwise while stirring thoroughly with a glass rod. The stirring was continued for 5 min, and then allowed to stand for 2 h. After adding 200 ml of water, stirring was continued for another 2.5 h. When the temperature dropped to room temperature, a calcium aluminum composite emulsion was obtained. The dynamic viscosity was measured and the measured value was 0.31 Pa·s. The calcium aluminum composite emulsion had a high rheological property.

[0034] Example 6 At room temperature and pressure, 14 g of calcium oxide and 6 g of aluminum oxide were ball-milled. The ball-milling method adopted was dry milling. The ball-milling beads used were agate beads with a diameter of 5 mm. The speed was set to 250 rpm. The ball-milling time was 3 h. To the ball-milled composite powder, 0.01 g of polyoxyethylene amide nonionic surfactant and 0.02 g of nonionic PAM were added in sequence, and 0.8 ml of propylene glycol was added dropwise while stirring thoroughly with a glass rod. The stirring was continued for 5 min, and then allowed to stand for 2 h. After adding 200 ml of water, stirring was continued for another 2.5 h. When the temperature dropped to room temperature, a calcium aluminum composite emulsion was obtained. The dynamic viscosity was measured and the measured value was 0.33 Pa·s. The calcium aluminum composite emulsion had a high rheological property.

[0035] Example 7 At room temperature and pressure, 14 g of calcium oxide and 6 g of aluminum oxide were ball-milled. The ball-milling method adopted was dry milling. The ball-milling beads used were agate beads with a diameter of 5 mm. The speed was set to 250 rpm. The ball-milling time was 3 h. 0.01 g of polyoxyethylene amide nonionic surfactant and 0.02 g of nonionic PAM were added to the ball-milled composite powder in sequence, and 0.8 ml of butanol was added dropwise while stirring with a glass rod, and the stirring was continued for 5 min, followed by standing for 2 h. After adding 200 ml of water, stirring was continued for another 2.5 h. When the temperature dropped to room temperature, a calcium aluminum composite emulsion was obtained. The dynamic viscosity was measured and the measured value was 0.30 Pa·s. The calcium aluminum composite emulsion had a high rheological property.

[0036] Example 8 At room temperature and pressure, 15 g of calcium oxide and 5 g of aluminum oxide were ball-milled. The ball-milling method was dry milling. The ball-milling beads were agate beads with a diameter of 5 mm. The speed was set to 250 rpm. The ball-milling time was 3 h. To the ball-milled composite powder, 0.02 g of polyoxyethylene amide nonionic surfactant and 0.02 g of nonionic PAM were added in sequence, and 1 ml of ethylene glycol was added dropwise while stirring thoroughly with a glass rod. The stirring was continued for 5 min, and then allowed to stand for 2 h. After adding 200 ml of water, stirring was continued for another 3 h. When the temperature dropped to room temperature, a calcium aluminum composite emulsion was obtained. The dynamic viscosity was measured and the measured value was 0.35 Pa·s. The calcium aluminum composite emulsion had a high rheological property.

[0037] Example 9 At room temperature and pressure, 15 g of calcium oxide and 5 g of aluminum oxide were ball-milled. The ball-milling method was dry milling. The ball-milling beads were agate beads with a diameter of 5 mm. The speed was set to 250 rpm. The ball-milling time was 3 h. To the ball-milled composite powder, 0.02 g of polyoxyethylene amide nonionic surfactant and 0.02 g of nonionic PAM were added in sequence, and 1 ml of ethylene glycol was added dropwise while stirring thoroughly with a glass rod. The stirring was continued for 10 min, and then allowed to stand for 2 h. After adding 200 ml of water, stirring was continued for another 3 h. When the temperature dropped to room temperature, a calcium aluminum composite emulsion was obtained. The dynamic viscosity was measured and the measured value was 0.36 Pa·s. The calcium aluminum composite emulsion had a high rheological property.

[0038] Example 10 At room temperature and pressure, the reaction steps are as follows: ① Under laboratory conditions, add a phosphogypsum powder (about 10 grams on a dry basis) to a 100 ml beaker, add the calcium aluminum composite emulsion prepared in Example 1 at a dosage of 1.7% and stir it for 0.5 h to make it evenly dispersed, and place it to stand for 6 to 24 hours. ② Leach the solidified phosphogypsum with pure water, and use a spectrophotometer to detect the initial concentration and post-treatment concentration of soluble phosphorus in the phosphogypsum according to the "National Standard for the Determination of Total Phosphorus in Water" (GB 11893-1989). ③ According to the "National Standard for the Detection of Fluoride Ions in Water" (GB 11894-2014), ion chromatography is used to detect the initial concentration and post-treatment concentration of soluble fluorine in the phosphogypsum. ④ Use a pH meter to monitor the initial pH value of the leaching solution. After 24 hours, place the phosphogypsum in the experiment further, and detect the above three indicators again at different times until two weeks after the solidification reaction. The experimental results show that the reaction is fully occurred within 0.5 hours, which means that the active ingredients in the emulsion can quickly react with the soluble phosphorus and fluorine in the phosphogypsum to form insoluble precipitates. The concentration of related substances in the leachate before and after 24 hours is shown in Table 1 below: Table 1:

[0039] According to GB 8978-1996 Integrated Wastewater Discharge Standard and GB 18599-2020 General Industrial Solid Waste Storage and Filling Pollution Control Standard, the standards of soluble phosphorus below 0.5 mg / L, soluble fluorine below 10 mg / L, and pH between 6-9 are met respectively. After two weeks, the soluble phosphorus test was below the detection limit, the soluble fluorine test value was 1.73 mg / L, and the pH value was stable between 7.1 and 7.3. The experiment proved the high efficiency of calcium aluminum composite emulsion in treating phosphogypsum, which can significantly reduce the concentration of soluble phosphorus and fluorine in a short time. The emulsion is expected to be used for the harmless treatment of phosphogypsum, and by reducing the concentration of soluble phosphorus and fluorine to meet environmental protection standards, so as to realize the resource utilization of phosphogypsum. The experiment also showed that the treated phosphogypsum maintained a stable low concentration state for a long time and was not prone to reverse release, which provided strong support for its practical application.

[0040] Embodiment 11 In the laboratory, simulated wastewater was prepared for treatment to observe the effect of the calcium aluminum composite emulsion prepared by the present invention. The simulated wastewater of the first group contained F- =400mg / L, (PO4) 3- =350mg / L, pH value = 4. According to the chemical balance calculation results, the implementation of adding 1% of the water body is very small, and the performance is excellent. Both sets of data meet the first-level standard of "Comprehensive Sewage Discharge Standard---GB8978-1996". Combined with the attached Figure 3 Experiments have shown that the calcium aluminum composite emulsion prepared by the present invention has a high efficiency in removing fluoride ions and phosphate ions in simulated wastewater. The emulsion is expected to be used in actual wastewater treatment, especially for wastewater containing high concentrations of fluoride ions and phosphate ions. The treated wastewater meets the first-level standard of the national comprehensive sewage discharge standard, indicating that the emulsion has practical application value.

[0041] The above contents are only for explaining the technical idea of ​​the present invention and cannot be used to limit the protection scope of the present invention. Any changes made on the basis of the technical solution in accordance with the technical idea proposed by the present invention shall fall within the protection scope of the claims of the present invention.

Claims

1. A method for preparing a calcium aluminum composite emulsion, characterized in that: include: After ball-milling calcium oxide and aluminum oxide powders to obtain composite powder, a surfactant is added for the first stirring. During the first stirring, a sustained-release agent is added. After standing, water is added to the reaction system for the second stirring. After natural cooling, a calcium aluminum composite emulsion is obtained.

2. The method for preparing a calcium aluminum composite emulsion according to claim 1, characterized in that: The mass ratio of calcium oxide to aluminum oxide powder is (14~15):(5~6).

3. The method for preparing a calcium aluminum composite emulsion according to claim 1, characterized in that: The ball milling was dry milling, agate beads were used as ball milling beads, the rotation speed was set to 250 rpm, and the ball milling time was 2 h-3 h.

4. The method for preparing a calcium aluminum composite emulsion according to claim 1, characterized in that: The surfactants are non-ionic polyoxyethylene amide and non-ionic polyacrylamide, and the mass ratio is (1~2): (2~3).

5. The method for preparing a calcium aluminum composite emulsion according to claim 1, characterized in that: The sustained-release agent includes one of ethylene glycol, methanol, propylene glycol or butanol, and the added amount is 3 ml to 5 ml of the sustained-release agent per 100 g of the composite powder.

6. The method for preparing a calcium aluminum composite emulsion according to claim 1, characterized in that: The mass ratio of the composite powder, nonionic polyoxyethylene amide and nonionic polyacrylamide (PAM) is 200: (1-2): (2-3).

7. The method for preparing a calcium aluminum composite emulsion according to claim 1, characterized in that: The first stirring time should be controlled within 5~10 minutes; the second stirring time should be at least 2~3 hours.

8. A calcium aluminum complex emulsion obtained by the preparation method of a calcium aluminum complex emulsion as described in any one of claims 1 to 7.

9. The use of the calcium aluminum composite emulsion according to claim 8 in the harmlessness of phosphogypsum, characterized in that: In the phosphogypsum treated with calcium-aluminum composite emulsion, the soluble phosphorus is less than 0.5 ppm, the soluble fluorine is less than 10 ppm, and the pH value is maintained at 8-10; after the treated phosphogypsum is exposed to air for 1 month, the removal rates of soluble phosphorus and soluble fluorine are 99.3% and 98.4% respectively.

10. The use of the calcium aluminum composite emulsion according to claim 8 in the treatment of phosphorus and fluorine wastewater, characterized in that: In the wastewater treated with calcium-aluminum composite emulsion, the phosphate concentration is lower than 0.5 mg / L and the fluoride ion concentration is lower than 10 mg / L.

Citation Information

Patent Citations

  • Stabilized remediation of lead-contaminated soil

    CN114985444A

  • Method for deeply curing soluble phosphorus and fluorine in ardealite through mechanical force ball milling

    CN116425437A

  • Preparation method and application of calcium oxide composite emulsion with high rheological property

    CN116693025A

  • High-activity lime milk as well as preparation method and application thereof

    CN117383841A

  • Road marker

    KR102397106B1